A high-output silk-based triboelectric nanogenerator with durability and humidity resistance. (April 2023) - He, Lixia; Zhang, Chuguo; Zhang, Baofeng; Gao, Yikui; Yuan, Wei; Li, Xinyuan; Zhou, Linglin; Zhao, Zhihao; Wang, Zhong Lin; Wang, Jie
Abstract: Triboelectric nanogenerator, as an energy harvesting device, is regarded as a promising technology to power distributed electronics of the Internet of Things (IoTs) by forming self-powered systems. However, humidity resistance and durability are the two issues should be addressed before its practical application. Here, a mulberry-silk based triboelectric nanogenerator (MS-TENG) with low-wear, humidity-resistant and high-output characteristics is proposed to harvest energy efficiently and economically. Benefitting from the fluffy structure and good triboelectric performance of mulberry silk, it achieves a high charge density under a low friction force and its energy harvesting efficiency improves by 10 times compared with previous works. Moreover, taking advantage of low friction force and hygroscopicity of mulberry silk, the output performance of MS-TENG is basically stable after 1, 500, 000 cycles or even under the relative humidity up to 90%. This work provides an efficient strategy for the long-term practical application of TENG in energy harvesting and powering IoTs. Graphical Abstract: Benefiting from the fluffy structure and good triboelectric performance of soft mulberry silk, the MS-TENG achieves a high charge density under the low friction force and its energy harvesting efficiency improves by 10 times. In addition, taking advantage of low friction force and hygroscopic of mulberry silk, the MS-TENG displays an excellent durability and humidity resistance. ga1 Highlights: A 10-fold increase in energy harvesting efficiency owing to fluffy structure and electron loss performance of mulberry silk. The transferred charges of MS-TENG do not decay even after 1, 500, 000 continuous operation cycles. The MS-TENG can keep stable even the relative humidity increases to 90% owing to the good hygroscopicity of silk. A wireless alarm system is realized to monitor wind speed by combining a double-layered MS-TENG with a power management.